(untitled) (Revista Contexto & Saúde, 2025)
Objective: to gather scientific evidence on suicide attempts and suicides among mothers of children with disabilities. Methods: this is an integrative review conducted in five databases, using the research question: “What is the scientific evidence on suicide attempts and suicides among mothers of children with disabilities?” The descriptors “Mothers”, “Suicide”, “Attempted Suicide”, “Suicide Attempt”, “Children with Disabilities” and “Disabled Children” were used. Four studies from different countries were included, published between 2018 and 2024, were included. The critical analysis and qualitative synthesis of the selected studies were carried out descriptively and organized into two categories. Results: mothers of disabled children face high levels of stress and depression, aggravated by marginalization and lack of support. The transition into adolescence of their children intensifies this emotional burden. It is essential to offer psychological support and practical resources to improve their quality of life. Psychological and financial support and support networks are essential to reduce stress. Final considerations: ensuring access to health services and flexible working conditions, as well as including families in policy formulation, can improve the life quality of these families and promote a more inclusive society.